PELATIHAN DESAIN PRODUK DALAM PEMASARAN DIGITAL PADA PEMUDA KARANG TARUNA DESA CIKAREGEMAN SELAMA COVID-19 - andi arfian; Ani Yoerani; Adelia Alvi Yana; Juarni Siregar; Syafianto Syafianto (Politeknik Negeri Sriwijaya, 2021)
Utilization of marketing technology during the pandemic requires broad insight in increasing digital marketing, especially during the pandemic period from the above problems, so community service activities are to add insight and use digital-based technology, especially during the Covid-19 period where human interaction is limited and as a solution that can be used as a solution. desired in this activity is to train youth youth to master product design techniques for marketing through social media and internet networks through the creation or design of product content which is interesting with digital marketing tools such as Fixellabs and Canva to produce broad marketing improvements and provide an understanding of optimizing Product Design Making in the form of banners and pamphlets as well as marketing product designs using social media as a marketing medium. This workshop was attended by 10 participants who are youth youth organizations from Cikarageman Village, Setu District, Bekasi Regency. The results achieved by the participants were very enthusiastic in participating. This training and the end of this training is an increase in the economy of the Village Youth and the village community at large during this Covid-19 pandemic.